IT governance : a pocket guide - Calder, Alan, 1957- (IT Governance Pub., 2007)
This new downloadable pocket guide in the Practical IT Governance series, is designed to provide the reader with a basic understanding of how an organization's Information Technology supports and enables the achievement of its strategies and objectives.